Review paperSkin care in children - Kmieć, Małgorzata L.; Urysiak-Czubatka, Izabela; Broniarczyk-Dyła, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Skin has an important role as a barrier against transepidermal water loss, mechanical trauma, UV radiation, allergens, microorganisms and penetration of irritating substances. Taking part in homeostasis, it plays one of the fundamental roles in adaptation to life. In newborn skin there are some anatomical and physiological differences, caused by skin immaturity, which are especially significant in premature and neonate children. These differences related to the skin include greater body surface area to volume ratio, thinner and more permeable stratum corneum, lower activity of sebaceous and sweat glands, and skin pH closer to neutral value. It causes normal barrier function disruption, skin permeability augmentation and immaturity of the thermoregulatory mechanisms. It can also induce skin hypersensitivity, higher prevalence of irritation and allergic reactions, which is why proper care and protection is so significant. Skin care practices should take into account anatomical dissimilarities and cosmetic products should be adjusted to age and skin condition. After a thorough examination pathologically changed skin needs individual treatment. This review article presents anatomical and physiological differences in the infant’s skin. Skin care practices for healthy and pathologically changed skin are also discussed. Key words: dermis, children, skin care, cosmetics.